Letter from Andrew M. Sessler to William A. Lester, Jr., October 19, 1976 - Sessler, A. M. (Andrew Marienhoff) (1976)
Letter from Andrew M. Sessler to William A. Lester, Jr. (1937-) about establishing a National Resource for Computation in Chemistry (NRCC). Sessler invites Lester to an NRCC workshop to be held at the Lawrence Berkeley Laboratory.
Keywords: Lester, William A., Jr., 1937-; Sessler, A. M. (Andrew Marienhoff); Lawrence Berkeley Laboratory. National Resource for Computation in Chemistry; Computational chemistry